2018
DOI: 10.1002/jhbp.577
|View full text |Cite
|
Sign up to set email alerts
|

Multinational validation of the American Joint Committee on Cancer 8th edition pancreatic cancer staging system in a pancreas head cancer cohort

Abstract: The 8th edition provides more even distribution with more powerful discrimination compared to the 7th edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…The AJCC staging system was revised for the eighth time since its first edition in 2018. Its validity was demonstrated in several studies [5][6][7]. The AJCC staging system always considered pancreatic cancers in terms of the whole pancreas, without dividing the pancreas according to the location, since pancreatic cancers in the head/uncinate process and those in the body/tail share the same prognosis and have comparable tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…The AJCC staging system was revised for the eighth time since its first edition in 2018. Its validity was demonstrated in several studies [5][6][7]. The AJCC staging system always considered pancreatic cancers in terms of the whole pancreas, without dividing the pancreas according to the location, since pancreatic cancers in the head/uncinate process and those in the body/tail share the same prognosis and have comparable tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients with PHC underwent the Kausch-Whipple procedure and standard lymphadenectomy along the right side of the superior mesenteric artery, the hepatoduodenal ligament, and the celiac trunk/upper pancreatic margin. PHC was confirmed histopathologically and classified according to the criteria of World Health Organization and the American Joint Committee on Cancer (AJCC) (13,14). Patients who underwent preoperative chemoradiation were excluded since it affects the ratio of fibrosis to cancer cells (15).…”
Section: Methodsmentioning
confidence: 99%
“…55,56 The 8th edition of the TNM staging system in exocrine pancreas, particularly PDAC, is generally well received and considered superior to the 7th edition, with more even distribution among stages and more powerful discrimination. [57][58][59][60][61][62] Yet slightly varied opinions and some refinements have been brought up in different studies. Two studies, 60,61 one from China and one from Germany, found that the new T classification had a significant advantage over the previous edition in predicting overall survival whereas the new N classification did not, which is opposite to the results of an international multicenter cohort study 62 where the revised N stage was highly prognostic, but the revised T stage was not.…”
Section: Carcinoma Of the Exocrine Pancreasmentioning
confidence: 99%